Opposition as victimhood in newspaper debates about same-sex marriage - Turner, Georgina; Mills, Sara; Van der Bom, Isabelle; Coffey-Glover, Laura; Paterson, Laura L.; Jones, Lucy (SAGE, 2018)
In this paper, we take a queer linguistics approach to the analysis of data from British newspaper articles that discuss the introduction of same-sex marriage. Drawing on methods from CDA and corpus linguistics, we focus on the construction of agency in relation to the government extending marriage to same-sex couples, and those resisting this. We show that opponents to same-sex marriage are represented and represent themselves as victims whose moral values, traditions, and civil liberties are being threatened by the state. Specifically, we argue that victimhood is invoked in a way that both enables and permits discourses of implicit homophobia